Quilombo Filipa no “novo tempo” dos projetos de intervenção desenvolvimentista no Maranhão. - Teles, Claudia (2017)
This work proposes to investigate the social situation of quilombo Filipa in “new times” of developmental interventions projects. The proposal, in general lines, discusses the intervention process of the State and other institutions using economic projects. The approach considers an ethnic group, which, being an autonomous economic unit, allows the study based on anthropological characteristics. In this perspective, are considered two concepts discussed in economic anthropology by Karl Polanyi, based on the definitions of two approaches, the substantive and the formalist perspectives; also on the social relationship between Filipa quilombo and other social situations. The basis of this study results of the narratives of the own social agents. As research instruments, direct observation, semi-structured interview, and oral history are used. I also used the Constitution of 1988, a legal provision that created conditions for quilombola communities to enter into the field of formal and social law from Article 68 of the Acts of Transitional Constitutional Provisions/ATCP. This fact put in discussion the policies and programs that have been extended to these groups, classified as “poor” or “low income”. The research intends to answer three questions: what is new in the economic, social and ethnic policies directed to the quilombola communities? Under what conditions do they become the target of such policies? What are the effects of these interventions on the quilombo Filipa’s economic and political organization? The study proposed, in this research, reveals that the proposals implemented in quilombo Filipa do not correspond to the real interests of the group, causing a silent process of political demobilization, because they are of an individual character, and do not consider social practices, group awareness and its observance of collective interests and benefits.